Rodent-borne Ljungan virus in dispersing Norwegian lemmings (Lemmus lemmus) - Hauffe, Heidi Christine; Rossi, C.; Rosso, Fausta; Girardi, M.; Recinella, G.; Voutilainen, L.; Vapalahti, O.; Rizzoli, Annapaola; Henttonen, H. (2012)
The Ljungan (picorna) virus (LV) was first isolated in 1998 from Swedish bank voles (Myodes glareolus), and has subsequently been in laboratory mice and rats, as well as many wild small mammal species, including mice, voles and lemmings, in Sweden, Denmark, Germany, USA, and most recently, Italy. Although it was initially put forward as a zoonotic agent of several human (primarily gestational) diseases, LV causes symptoms in the rodents themselves; however, its effect on rodent ecology and population dynamics is unknown. Norwegian lemmings (Lemmus lemmus) have cyclical population dynamics and thus, may be affected by LV. As a first attempt at addressing this question, we present some results of RT-PCR screening for its presence and prevalence in Norwegian lemmings from northern Finland, caught before, during and after a major dispersal event in spring 2011.